Effectiveness of Disaster Management Programs: a Collaborative Governance Analysis of Flood Response in North Kalimantan Province - Amriampa, Andi; Ibrahim, Akmal; Hasniati , Hasniati; Abdullah, Tang; Iskandar, Didik (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Flood disaster is a significant hydrometeorological risk in North Kalimantan Province, demanding effective management programs. This research aims to analyze the effectiveness of flood disaster management programs in North Kalimantan Province with a focus on collaborative governance aspects. Using a qualitative approach with a case study method, this research collected data through in-depth interviews, observations, and documentation from key stakeholders, including the BPBD, local government, TNI/Polri, and community elements. The analysis was conducted through a program effectiveness framework that includes input, process, output, and outcome stages. The results showed that the disaster management program was quite effective at the output stage, especially in the emergency response aspect. However, effectiveness at the input and process stages still faces significant obstacles. Limited resources (input) and weak coordination, incidental collaboration, and unstructured participation (process) are the main obstacles to achieving long-term outcomes, namely increased community resilience. This research concludes that the effectiveness of the program is hampered by the suboptimal implementation of sustainable collaborative governance. It is necessary to strengthen the joint commitment between institutionalized stakeholders to improve the overall effectiveness of the program.